Blunted apoptosis of erythrocytes in mice deficient in the heterotrimeric G-protein subunit Gαi2 - Bissinger, Rosi (2016)
Fil: Bissinger, Rosi. University of Tuebingen. Vascular Medicine and Physiology. Institute of Cardiology; Alemania